The Implementation of Scaffolding Game Media To Improve Student Learning Outcomes In SDN 27 Pontianak - Lidia Muri (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2020)
The study aimed to describe the implementation of scaffolding game media to improve learning outcomes of thematic learning in VI-grade at SDN 27 Pontianak (Pontianak 27 State Elementary School). The research method used by researchers was descriptive. The form of research was Classroom Action Research. Data collection techniques in this study were observed and questionnaire responses of students. Research collection tools in the form of observation sheets. This research was conducted for two cycles. The results of this study included the ability of teachers to plan learning using scaffolding game media, namely cycle I (85.81%), increased 9.94% in cycle II (95.75%) with an average value of 87.41% (category very good). The ability of teachers to implement learning in the first cycle (76.19%) increased by 16.27%, and the second cycle to 92.46% with an average value of both cycles of 92.46% (very good category), an increase of 16, 27%. The first cycle learning activities with an average of 76.45% increased by 14.84% in the second cycle with an average value of 89.07%, the average score of the second cycle learning activities 81.65% (once category) and the questionnaire response positive students as much as 85.93% (very good category). The first cycle learning outcomes test with an average value was 76.45, and the second cycle was 79.48%, the average value of the learning outcomes test was 77.97% (good category), and an increase of 30.3%. Based on data analysis of student learning outcomes, shows that the use of Scaffolding Game media can improve student learning outcomes.